2017
DOI: 10.1016/j.healthpol.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Implementing shared-decision-making for diabetes care across country settings: What really matters to people?

Abstract: (Word number: 250)Diabetes is one of the leading causes of mortality, disability and expenditure worldwide. Growing evidence of improved outcomes (patient/professional satisfaction and some evidence on controlled weight, blood glucose and blood pressure) supports shareddecision-making (SDM) as an effective primary care intervention for diabetes. However, only a few countries have actually adopted it (e.g. UK). In other European countries there is awareness that patients play a crucial role in decision-making, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…An health economic technique, such discrete choice experiments (Clark MD, et al 2014) could find a new use to support the development of person-centered care pathways in MS according to patient preferences and experience of care (Anagnostou D, et al 2017). A DCE-based patient relevant outcome indicator could also be developed and applied to evaluate the benefits attached to new person-centered care pathways compared to current care (for example see application to diabetes (Tinelli M, et al 2017) and also monitor their performance (alongside other clinical and health status indicators) against defined benchmarks (Tinelli M, et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…An health economic technique, such discrete choice experiments (Clark MD, et al 2014) could find a new use to support the development of person-centered care pathways in MS according to patient preferences and experience of care (Anagnostou D, et al 2017). A DCE-based patient relevant outcome indicator could also be developed and applied to evaluate the benefits attached to new person-centered care pathways compared to current care (for example see application to diabetes (Tinelli M, et al 2017) and also monitor their performance (alongside other clinical and health status indicators) against defined benchmarks (Tinelli M, et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, the situation is improving and clinical data should be rapidly made available ( 32 ). On the other hand, electronic health records collected at the point of care using a valid patient ID were noted in a second group of participants from Belgium ( 36 ), Cyprus ( 37 ), England ( 30 ), Italy ( 31 ), Malta ( 38 ), Poland ( 39 ), Romania ( 40 ) and Slovenia ( 41 ). For England, the advantages offered by an expanding network of general practitioners included the possibility of linking and comparing items from different comorbid conditions stored in the same database ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…When comparing Cyprus to an alternative European setting such as England where person centred practices are already in place we found that Cypriots valued choosing alternative SDM services compared to their 'current' option, whereas the English preferred their status quo to other services. 36 Several of these issues can be imputed to the lack of a universal coverage system. Indicatively, patient campaigns, medical audit and other efficiency enhancement activities such as electronic prescribing, performance management have been programmed once the NHIS is on, therefore is anticipated that this will address, at least to a certain degree some of our findings.…”
Section: Discussionmentioning
confidence: 99%